Attractive particle interaction forces and packing density of fine glass powders - Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Blümel, Christina; Wirth, Karl-Ernst; Peukert, Wolfgang; Pöschel, Thorsten (Scientific Reports, 2014)
We study the packing of fine glass powders of mean particle diameter in the range (4-52)μm both experimentally and by numerical DEM simulations. We obtain quantitative agreement between the experimental and numerical results, if both types of attractive forces of particle interaction, adhesion and non-bonded van der Waals forces are taken into account. Our results suggest that considering only viscoelastic and adhesive forces in DEM simulations may lead to incorrect numerical predictions of the behavior of fine powders. Based on the results from simulations and experiments, we propose a mathematical expression to estimate the packing fraction of fine polydisperse powders as a function of the average particle size.